Methodical Maintenance Ecological and Social Assessment of Condition Recreation Areas Agrosphere - Рідей, Н. М.; Хітренко, Т. Ф. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
There are analyzed the existing methodology for environmental assessment of soil; ground and surface waters in rural areas; social and natural systems in the agrosphere; including anthropogenic and production; welfare and recreational load and social; recreational; tourist and environmental support for the organization and development recreational kinds of activity in the territories agrosphere. There are determined indicators and parameters of scientific and methodological support which are needed for assessment the ecological state of recreational areas of agrosphere. There are developed structurallogical scheme of organization environmental and social assessment of recreational areas of agrosphere; that allows to adapt the existing scientific and methodological recommendations of leading scientific institutions in Ukraine to ensure the weekend; current and future information data of research for the justify and construction of systems for environmental monitoring of recreational territories of agrosphere.